Agregar un numeral al artículo 630 del código orgánico integral penal, para establecer la improcedencia de la suspensión condicional de la pena en delitos de acción privada y contravenciones - Quishpe Taipe, José Elías (2017)
This research work whose theme is "ADD A PARAGRAPH TO ARTICLE 630 OF COMPREHENSIVE ORGANIC PENAL CODE TO ESTABLISH THE ILLEGALITY OF THE CONDITIONAL SUSPENSION OF PUNISHMENT OF CRIMES OF PRIVATE ACTION AND VIOLATIONS" so that the objective of this research it is aimed at legal and critical analysis of procedures and claims in the application of the functions of the Office, as well as establishing a legal reform Comprehensive Organic Code of Criminal procedure, to address an issue of legal and social reality Ecuador. Today the new rules governing criminal matters in Ecuador provided several mechanisms and alternative procedures for resolving conflicts in this area, this evolution in Ecuador's criminal law not only demonstrates the intention that the processing is agilité the various complaints, but also rebelling certain indulgences in the treatment of crimes in their prosecution. These new figures are implemented in the Code of Integral Criminal conditional suspension of sentence, figure in the main leads to forgiveness of imprisonment and replacing certain conditions, for which the person already convicted and declared guilty elapsed after the whole process, you must meet certain requirements to qualify for this benefit. This thesis Legal Research is structured as follows: First a Conceptual Framework, comprising concepts and definitions of sanctions, conditional suspension, among other items that will give greater prominence to the proposed theme; doctrinaire framework, covering the doctrines of writers and scholars on how to obtain the conditional suspension of sentence. Legal framework, including the analysis of the Constitution of the Republic of Ecuador, the Organic Code Integral Criminal, the Organic Code of the Judicial Function and then have a Comparative Legislation as it helped me to make an analysis of the subject from other countries and to extract the most positive. Secondly the research work includes a field study in which surveys and interviews are developed connoisseurs of law in helping me determine or contrast the objectives and hypotheses raised. Third after the analysis of field research we proceeded to the conclusions and recommendations and finally to a legal proposal necessary for the solution of the problem.